Phytoextraction of cadmium from soils treated with sewage sludge - Maxted, Andrew P. (2003)
The efficacy of phytoextraction strategies were tested by pot and field trials on soil contaminated with heavy metals, including Cd, derived from long-term disposal of sewage sludge. The strategies investigated were: i) the use of hyperaccumulators; ii) chemically-enhanced uptake using arable species and iii) the use of short rotation coppice (SRC). Chemical interventions including EDTA, chloride salts, HCl and herbicide were used to enhance uptake by arable and SRC species. Tissue Cd concentrations in the Ganges population of Thlaspi caerulescens were lower than reported in other studies; the mean Cd concentration was 265 mg kg". It was deduced that Cd uptake was limited by a low Cd2+ concentration in soil and the rate at which solution Cd was replenished. High rates of plant mortality were observed, raising questions over the successful husbandry of T. caerulescens for phytoextraction. Chemical interventions produced significant increases in metal uptake by arable and SRC species. For example, Cd uptake by Z. mays following application of 10 mmol EDTA kg'' and by Salix caprea x cineria x viminalis following combined application of EDTA and HCI. However, concentrations were still well below those required for successful remediation. Furthermore downward migration of metal was observed through the soil profile following EDTA application. For example, the soil Cd concentration in the 0- 10 cm profile was reduced from 32.0 to 25.5 mg kg' seven months after application of 10 mmol EDTA kg'', yet only 1% of this reduction could be accounted for by Z. mays Cd off-take. Realistic estimates for phytoextraction timescales and costs were made in line with legislative thresholds. Overall the time required to reduce total soil Cd concentrations below 3 mg kg-1 was large and the costs were prohibitive. For example, although Cd off-take by Ganges was greater than for any of the other species tested, it was estimated that well over one century would be required to reach target metal concentrations.